DIGITAL PLATFORM-BASED DIFFERENTIATION TEACHING MODEL IN ELEMENTARY SCHOOLS IN LAMPUNG - M. Agus Kurniawan; Suci Hartati (CV JK Riset Publishing Group, 2025)
This study developed a differentiated learning model based on digital platforms to enhance educational quality in elementary schools in Lampung through a Research and Development (R&D) approach using the ADDIE model. The research sample comprised three elementary schools in Bandar Lampung, involving 15 teachers from grades 4-6, three principals, and three educational technology experts as validators. Data were collected through validated questionnaires (α=0.85), structured interviews, classroom observations, achievement tests, and MSLQ motivation questionnaires. Analysis employed mixed methods concurrent embedded design with descriptive statistics, paired sample t-tests, and Braun & Clarke thematic analysis. Findings revealed a significant 23.4% improvement in student academic achievement (p<0.05), with the digital platform demonstrating 87.3% accuracy in identifying individual learning styles. Teachers' pedagogical competency transformation achieved an 86.7% confidence level in using educational technology. Student learning motivation increased with large effect size (Cohen's d=1.23), particularly in intrinsic motivation and self-regulation dimensions. A strong positive correlation (r=0.78) was identified between gamification features and student engagement. Despite encountering challenges related to digital divide and infrastructure limitations, the model demonstrates high replication potential through integrated approaches involving multi-level stakeholders. This research contributes significantly to the development of digital differentiated learning theory and provides a practical framework for sustainable educational technology implementation.